Evaluation of Brawijaya University’s Interior Physical Environment Effect on Library Users’ Comfort - Debri Haryndia Putri (Jurnal VOK@SINDO, 2016)
A space affects humans not physically but also psychologically. Therefore, we are often familiar with the term "comfortable" when dealing with peaceful feeling of being inside a space. Saunders (2015) states that out of 19 reasons why people visit a library, physical space has become the second reason after the library’s collection. This indicates that the number of visits as well as the length of time for the visit are also influenced by the condition of the library interior. Comfort in the library space is still the main thing that determines the users’ interest when visiting the library. This study aims to evaluate the effects of the elements that make up a library’s interior design on the comfort perceived by students as users. Interior design elements as indicators of visual comfort to be studied are the visual variables, flexibility, socialization comfort, thermal and acoustic. The importance of understanding users’ psychological condition because of physical environment of the library can make a university’s library become a pleasant and comfortable space for the academic community to support teaching and learning process.